2013
DOI: 10.1002/cbic.201300281
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Substrates and Probes for IgA1 Protease Activity

Abstract: Bacterial meningitis is a severe infectious disease with high mortality. Gram-positive and Gram-negative bacteria that cause meningitis secrete immunoglobulin A1 (IgA1) proteases to assist in mucosal colonization, invasion, and immune evasion. IgA1 proteases have unique selectivity, with few reported substrates other than IgA1 from human tissue. Here we describe the design, characterization, and application of peptide substrates for diverse IgA1 proteases from Neisseria, Haemophilus, and Streptococcus bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Amongst others, we have identified the serine protease HtrA, an important virulence factor (Loosmore et al, 1998), as well as the vaccine candidates OMP 26 and protein D (Pichichero et al, 2010) to be present in OMVs derived from all strains tested. In contrast, other proteins like the protective surface antigen D15, a vaccine candidate (Loosmore et al, 1997), as well as the IgA1 protease, an important virulence factor (Choudary et al, 2013), were exclusively found in NTHi 2019-R OMVs.…”
Section: Lipidomic and Proteomic Analyses Reveal Similar But Not Idenmentioning
confidence: 90%
“…Amongst others, we have identified the serine protease HtrA, an important virulence factor (Loosmore et al, 1998), as well as the vaccine candidates OMP 26 and protein D (Pichichero et al, 2010) to be present in OMVs derived from all strains tested. In contrast, other proteins like the protective surface antigen D15, a vaccine candidate (Loosmore et al, 1997), as well as the IgA1 protease, an important virulence factor (Choudary et al, 2013), were exclusively found in NTHi 2019-R OMVs.…”
Section: Lipidomic and Proteomic Analyses Reveal Similar But Not Idenmentioning
confidence: 90%
“…The limitations of existing drug discovery efforts targeting IgA proteases led us to explore alternative substrates as potential starting points for HTS. In prior work, we developed the first synthetic Förster resonance energy transfer (FRET) probe for monitoring IgA1P activity, molecule F2.2 (Figure c) …”
mentioning
confidence: 99%
“…F2.2 incorporates a peptide sequence from an autoproteolytic site of Neisseria gonorrheae type 2 IgA1P. F2.2 is cleaved by a variety of IgA1Ps from Gram-negative pathogens, including H. influenzae . We previously demonstrated the compatibility of F2.2 with a 384-well HTS format using Neisseria meningitidis IgA1P.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using various hybrids of IgA as substrate show that most but not all IgA1 proteases will cleave a postproline peptide bond in one half of the IgA1 hinge, even when seen in the context of the IgA2 Fc (Senior et al, 2000). Fluorescent peptide probes for the rapid, sensitive, and quantitative detection of IgA1 protease activity were reported (Choudary et al, 2013).…”
Section: Enzymatic Properties Of Iga Proteasesmentioning
confidence: 98%